DETERMINASI FRAUDULENT FINANCIAL REPORTING BERDASARKAN PERSPEKTIF FRAUD HEXAGON DAN UKURAN PERUSAHAAN - Hartsetyo, Angelia Putri; Diandra, Prita Karina (LPPM Universitas Bina Bangsa, 2025)
The fraud hexagon perspective and firm size are needed to detect fraud in financial reporting. The fraud hexagon consist of six elements, namely: pressure, opportunity, rationalization, capability, arrogance, and collusion. This study aims to detect fraudulent financial reporting using the fraud hexagon perspective and company size. The research sample used is property and real estate sector companies listed on the Indonesia Stock Exchange in the period 2020 to 2022. There are 54 research samples selected using purposive sampling technique. The analysis technique used is multiple linear regression analysis using the SPSS 26. The results of the study indicate that individually only the pressure variable with the proxy external pressure and the opportunity variable with the proxy nature of industry have influence on fraudulent financial reporting. While other variables, namely rationalization, capability, arrogance, collusion, and firm size have no influence on fraudulent financial reporting